Organization of the educational process of future specialists in graphic design using digital technologies - Olena Yefimenko (Scientific notes of the pedagogical department, 2023)
Today we live in the era of global digitalization of society. The rapid development of technologies and digitalization captures an ever-increasing spectrum of human activity, including educational and creative areas. Digitazation is rethinking approaches to the organization of the educational process, creative and project activities at the global level. Digital technologies should be understood as one of the tools in design activity in contemporary art, as well as an area for creaƟng immaterial virtual products. The purpose of the article is to highlight the impact of digital technologies on the organizaƟon of the educational process of graphic design specialists. Materials and methods. To achieve the research goal, a set of theoreƟcal methods was used: analysis and generalizaƟon of scienƟfic and methodical sources for theoretical substantiation of research problems, modeling, and synthesis of the obtained data. Research results. The main goal of design educaƟon is the formaƟon of a qualified specialist, a person capable of mastering cultural experience and modern technologies, including digital ones. Design is a special type of activity in which innovative methods of project soluƟons and modern digital technologies are widely used and developed. Thus, the level of technological development and digitalization today is more than ever stimulating the development and promotion of design education. Digitazation promotes the introducƟon of webinars and video conferences into the educational process, it has changed the form and type of organization, as well as the availability of educational materials. Interactive media resources and digital technologies are increasingly used in modern design education. As with any evolving system, digitazation has a number of disadvantages and advantages. On the one hand, the development of digitalization gives designers an unlimited field for creativity and work. On the other hand, a number of problems and diﬃculties appear. For example, changes in the form of organization of work with the audience, including features and diﬀerences of physical objects and their digital copies, copyright, etc.